Research progress on the current status of respiratory pathogen infections and their detection methods - Zhu, Fuhong; Peng, Mei; Chen, An’ning; Zhu, Qian-Ying (Frontiers in Microbiology, 2026)
Respiratory tract infections (RTIs) are among the most prevalent diseases in human society and pose a major global health threat, affecting millions annually. A wide range of pathogens, primarily viruses and bacteria, cause RTIs. These infections often present with similar symptoms, which limits effective clinical treatment. Extensive research has addressed RTIs, with ongoing discussion regarding their current status and advancements in detection technologies. Novel laboratory methods that offer rapid, sensitive, and specific results now supplement traditional diagnostic approaches. In this review, we summarize the infection characteristics and detection methods of common respiratory pathogens, evaluate the effectiveness and limitations of current detection methods, and aim to promote advancements in laboratory diagnosis and explore the potential of emerging technologies in this field.